Effect of number of layers and deposition time on layer-by-layer (LbL) composite forward osmosis membrane - Annie Lau, Ying Ying; Mazrul Nizam, Abu Seman (Elsevier Ltd, 2020)
Forward osmosis (FO) refers to the osmotic process for water transfer through a semipermeable membrane that results in the separation of water from dissolved solutes. This method has been explored due to low fouling propensity and low energy requirement since the driving force is an osmotic pressure gradient between the feed and draw solutions. This research focused on determining the optimum FO membrane by controlling the number of polyelectrolyte bilayers and deposition time of membrane for seawater desalination. Poly(diallyl-dimethylammonium chloride), PDADMAC and poly(sodium 4-styrenesulfonate), PSS were used as active monomers to generate a thin layer on the ultrafiltration membrane support through layer-by-layer (LbL) deposition method. The FO lab-scale experiment was performed by using 1.75 M of sodium sulphate (Na2SO4) as draw solution and deionised water (DI) as feed. This research was conducted based on the different number of bilayers (5, 10, and 15 bilayers) and deposition time (5, 10, and 15 min) which affected the water flux. After the best parameters were obtained, treatment on synthetic seawater (35 g/L of NaCl) was conducted, and the results were compared with that of real seawater. Among the modified membranes, it was found that the membrane 5FO15 with 5-bilayers of polyelectrolytes and 15 min of deposition time exhibited the highest water flux (4.75 L/m2∙h). The membrane exhibited a lower water flux for seawater than synthetic seawater due to the existing of other solutes which may contribute to membrane fouling. From this research, the polyelectrolyte membrane exhibited a high potential of treating seawater in Malaysia by FO process which is a good option of water treatment.